Divine Presence and Community: A Commentary on the Book of Leviticus - Kalluveettil, Paul (Journal of Dharma, 2020)
Gorman H. Frank, Jr., Divine Presence and Community: A Commentary on the Book of Leviticus, Michigan, Grand Rapids: W. B. Erdmans Publishing Co., 1997, pp.xii+163; 18.00.